1994
DOI: 10.2105/ajph.84.7.1086
|View full text |Cite
|
Sign up to set email alerts
|

The validity of self-reported smoking: a review and meta-analysis.

Abstract: OBJECTIVES. The purpose of this study was to identify circumstances in which biochemical assessments of smoking produce systematically higher or lower estimates of smoking than self-reports. A secondary aim was to evaluate different statistical approaches to analyzing variation in validity estimates. METHODS. Literature searches and personal inquiries identified 26 published reports containing 51 comparisons between self-reported behavior and biochemical measures. The sensitivity and specificity of self-report… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
1,027
11
12

Year Published

1996
1996
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 1,546 publications
(1,086 citation statements)
references
References 38 publications
18
1,027
11
12
Order By: Relevance
“…Self-reports of hypertension, hypercholesterolemia, and diabetes are likely related to one's access to health care, though we controlled statistically for variations in access to care by controlling for health insurance status and having a usual source of care. Furthermore, several studies have reported agreement between self-reported diabetes, hypertension, smoking, and alcohol consumption and medical record data or biochemical measures [72][73][74][75]. There is less agreement between selfreported high cholesterol and medical record data [76].…”
Section: Discussionmentioning
confidence: 99%
“…Self-reports of hypertension, hypercholesterolemia, and diabetes are likely related to one's access to health care, though we controlled statistically for variations in access to care by controlling for health insurance status and having a usual source of care. Furthermore, several studies have reported agreement between self-reported diabetes, hypertension, smoking, and alcohol consumption and medical record data or biochemical measures [72][73][74][75]. There is less agreement between selfreported high cholesterol and medical record data [76].…”
Section: Discussionmentioning
confidence: 99%
“…Measurements of nicotine-related biomarkers have often been used to validate questionnaire-derived data on smoking and exposure to ETS (Patrick et al, 1994). However, systematic multivariate modelling of potential factors influencing these biomarkers including estimation of the effect size in population-based samples is still missing.…”
Section: Discussionmentioning
confidence: 99%
“…Among cigarette smokers, the number of cigarettes used in the last day measures intensity (ranging from 0 to 20). Although U.S. studies find that self-reported smoking is generally accurate (Patrick et al, 1994), the validity of such items in low-income nations is less clear, and the items may reflect differential reporting by SES. Lacking physiological measures, survey responses remain the commonly accepted source of nearly all data on global patterns of tobacco prevalence.…”
Section: Variablesmentioning
confidence: 99%